Minimum alveolar concentration of isoflurane in dogs administered two morphine doses - Coelho,Karina (2017)
ABSTRACT: This study aimed to evaluate the effects of intramuscular 0.5mg kg-1 (MOR0.5) and 1.0mg kg-1 (MOR1.0) morphine premedication on the minimum alveolar concentration of isoflurane (ISOMAC) in dogs. Eighteen client-owned female dogs were scheduled for elective ovariohysterectomy. Dogs received intramuscular MOR0.5 or MOR1.0 as premedication and propofol IV for induction of anesthesia. Isoflurane was delivered for maintenance of anesthesia and dogs were maintained under normocapnia and normothermia. Determinations of the ISOMAC were conducted by use of the “up-and-down” method. Noxious stimulus (placement of Backhaus towel clamps, a midline skin incision and subcutaneous tissue dissection) was delivered approximately 50 minutes after premedication with MOR0.5 or MOR1.0. The calculated ISOMAC was 0.98±0.15% in MOR0.5 and 0.80±0.08% in MOR1.0. The ISOMAC was significantly lower in MOR1.0 compared with MOR0.5 (P=0.010). Results of this study suggested that intramuscular premedication with morphine 0.5 and 1.0mg kg-1 decreases the ISOMAC in a dose-related manner in dogs.